Condylomata Acuminata in Adolescent Girl 19th Years Old Successful with Multimodality Therapy and Combination with HPV Vaccination: A Case Report - Dwi Sabtika Julia; Qaira Anum; Rina Gustia (HM Publisher, 2021)
Background: Condylomata acuminata (KA) or better known as genital warts disease is a genital area infectious disease caused by Human papilloma virus (HPV). The highest prevalence infection of the condylomata acuminata occurs during active sexual periods, namely age 17-33 years, with the peak occurring at the age of 20-24 years. Currently HPV 16 and 18 are known to cause malignancy in the genital and anogenital region including cervical cancer and anal cancer, while HPV 6 and 11 are the cause of 90% of condylomata acuminata. HPV is linked to the findings of 500,000 new cases of cervical cancer and 250,000 deaths from cervical cancer each year worldwide.1 Case report: One case of condylomata acuminata in a 19-year-old adolescent girl with a major complaint of warts around her genitals that felt itchy and gradually getting bigger since 2 weeks ago. Patient was a student and unmarried. History of sexual contact with men with genito-genital without using condoms since 5 months ago. Venereological state : on the vulva and perineal there were multiple vegetations with verucose surfaces with the largest size 0.8 cm x 0.5 cm x 0.1 cm and the smallest size 0.2 cm x 0.2 cm x 0.1 cm. Acetowhite examination result was positive and PCR examination results found positive HPV types 6,11,16 and 18. Discussion: Patients are diagnosed to condylomata acuminata with a history of free sex at an early age. The condylomata acuminata experienced by patients was type 6,11,16 and 18. These types of 16 and 18 HPV are know to cause malignancy in the genital and anogenital region including cervical cancer and anal cancer.